Effects of Flotation Deinking on the Removal of Main Colors of Oil-Based Inks from Uncoated and Coated Office Papers - (:unkn) unknown (NORTH CAROLINA STATE UNIV DEPT WOOD & PAPER SCI, 2013)
This paper presents the results of trials to evaluate the color-stripping behaviour of offset printing colors and the effect of coating on deinking performance. Oil-based four-color inks were separately printed as base printing on coated and uncoated white poster paper, and then extensive pulping and deinking processes were carried out. Standard offset printings were conducted on paper samples using cyan, magenta, yellow, and black colors (CMYK), and the effects of deinking efficiency on the removal of each color were analysed. The pulps were made at Micro-Maelstrom Laboratory Pulper at specified conditions with and without bleaching agents. Formamidin sulfinic acid and hydrogen peroxide formulation were used as reductive and oxidative bleaching agents, respectively. Flotation deinking and thickening of pulp were practiced using Degussa flotation and thickening cell. The changes in the optical properties, such as brightness, whiteness, and color value (CIE L*, a*b*) of deinked pulp were determined. It was found that optical properties of color-stripped pulps from coated papers were better than that of uncoated office papers. However, yield was quite low in coated papers since fillers were lost during flotation process. Cyan color was found to be the most difficult one in four main color printing inks stripping out in deinking process.
Keywords: Paper recycling; Flotation deinking; CMYK offset printing; Color stripping; Coating; SURFACE; WATER; PULP